Comparative Study of Digital Modulation Techniques - Narula, Suneet (My University, 2008)
Although a significant portion of communication today is in analog form, it is being replaced rapidly by digital communication with the next decade most of the communication will become digital, with analog communication playing a minor role. In the present work digital communication system is being used as it provides the capability for information transmission that is both efficient and reliable. Digital modulation techniques may be classified in to coherent and non coherent techniques, depending on whether the receiver is equipped with a phase recovery circuits or not. The phase recovery circuit ensures that the oscillator supplying the locally generated carrier wave in the receiver is synchronized to the incoming data stream in the transmitter. We discuss all the digital modulation techniques in detail. For convienenance for the present study BPSK, QPSK, QAM, and OFDMA for comparison threre are modulation techniques used in many new digital data transmission systems such as digital video broadcasting, digital audio broadcasting and wireless local area networks. The parameters like symbol error rate, bit error rate and power spectral density for comparison. All these techniques, with the emphasis on bit error rate, average probability of symbol error commited by receiver in the presence of additive white noise and various power and bandwidth considerations. We analyzed these techniques by using modeling. We simulate models using Matlab 6 version. The comparative study of digital modulation was done with respect to the parameters; bit error rate, symbol error rate and power spectral density.
Keywords: Digital Modulation Techniques; Digital Design